Toxic metals impact gut microbiota and metabolic risk in five African-origin populations - Julianne A. Jorgensen; Candice Choo-Kang; Luyu Wang; Lina Issa; Jack A. Gilbert; Gertrude Ecklu-Mensah; Amy Luke; Kweku Bedu-Addo; Terrence Forrester; Pascal Bovet; Estelle V. Lambert; Dale Rae; et al. (Gut Microbes Reports)
Underlying mechanisms by which exposures to toxic metals/metalloids impact obesity and type 2 diabetes (T2DM) risk remain largely unknown. Gut microbiota have been strongly associated with cardiometabolic risk. To assess relationships between high metal exposures, gut dysbiosis, and metabolic dysregulation, we analyzed associations among gut microbiome taxa, dichotomized metal levels (arsenic, lead, mercury, cadmium), clinical measures (BMI, fasting blood glucose, blood pressure), and diagnoses (hypertension, obesity, diabetes) in 178 African-origin adults (52% female, mean age = 43.0 ± 6.4 years) from Ghana, South Africa, Jamaica, Seychelles, and USA. High vs. low lead and arsenic levels had a significant effect on beta diversity (p < 0.05). Seventy-one taxa were associated with high lead levels: 30 with elevated BMI, 22 with T2DM, and 23 with elevated fasting blood glucose (p < 0.05); 115 taxa were associated with high arsenic levels: 32 with elevated BMI, 33 with T2DM, and 26 with elevated blood glucose (p < 0.05). Porphyrin metabolism was the most enriched metabolic pathway in taxa associated with higher lead and arsenic exposure. These data provide the first findings from African-origin adults that demonstrate the association between the gut microbiome with lead and arsenic exposure and obesity and T2DM risk.